Essere genitori. Tra limiti legislativi e interessi (fondamentali) del minore (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Judgments no. 32 and 33 of 2021 represent the last stage of a long process of judicial review of Law no. 40/2004. Compared to the past, in the most recent cases, the Italian Constitutional Court used a different decision-making model, declaring the issues of constitutionality to be inadmissible because of the plurality of possible regulatory solutions and the ethical and social complexity of the topics involved. At the same time, however, the Court called for an urgent and undeferrable intervention by the Parliament. This paper will analyse, on the one hand, the substantive aspects of the two decisions and, on the other hand, the formal aspects linked to the decision-making technique adopted by the Constitutional Court, as well as the possible follow-up of judgement no. 33/2021.
Keywords: Parenting; assisted reproduction; surrogacy; best interest of the child; same-sex parenthood